Kewenangan Notaris Terhadap Akta Kuasa Jual Sebagai Tindak Lanjut Dalam Ikatan Jual-Beli - Moch. Syamsudin; Dwi Nensy Permata Soeyoto (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The transfer of land rights cannot be separated from the Sale and Purchase Agreement, which is usually accompanied by a Power of Sale. Based on the Minister of Home Affairs Number 14 of 1982 in conjunction with Article 39 paragraph 1 letter d the Selling Authorization is prohibited by the sanction of the process of turning his name rejected by the land office. Based on the description above, it will be investigated why the selling power of attorney is still made by a notary even though there are provisions that prohibit it and how legal protection is for the parties who have made the transfer of land rights by using the selling power. This research is a normative juridical research that is researching legal literature materials, equipped with legal and conceptual approaches. The results of the study, that the making of a Notary Sale and Purchase Agreement deed is not only limited to expressing the will of the parties. Based on Article 16 number (1) letter a UUJN, a Notary has the obligation to protect the interests of the parties in it by making a selling power of attorney. However, the problem is that the Land Office often refuses to process the name transfer if the Sale and Purchase Deed made by the PPAT is based on a Selling Authorization. To avoid this, the Notary inserts a selling power of attorney clause in the Sale and Purchase Agreement. From this conclusion, it is suggested that the selling power of attorney be handled wisely by the land office.Keywords: Power of Sale, Pijb, Transfer of Name AbstrakPengalihan hak atas tanah tidak lepas dari Perjanjian Ikatan Jual Beli, yang biasanya diiringi dengan Kuasa Jual. Berdasarkan Menteri Dalam Negeri Nomor 14 Tahun 1982 jo Pasal 39 ayat 1 huruf d Kuasa Jual dilarang dengan sanksi proses balik namanya ditolak oleh kantor pertanahan. Berdasarkan uraian di atas, akan diteliti mengapa Kuasa Jual tetap dibuat notaris meskipun terdapat ketentuan yang melarang dan bagaimana perlindungan hukum terhadap para pihak yang melakukan peralihan hak atas tanah dengan memakai kuasa jual. Penelitian ini merupakan penelitian yuridis normatif yakni meneliti bahan hukum pustaka, dilengkapi dengan pendekatan undang-undang dan konseptual. Hasil penelitian tersebut, bahwa pembuatan akta Perjanjian Ikatan Jual Beli Notaris tidak hanya sebatas menuangkan kehendak para pihak saja. Berdasarkan Pasal 16 angka (1) huruf a UUJN, Notaris mempunyai kewajiban melindungi kepentingan para pihak di dalamnya dengan cara membuat kuasa jual. Namun kendalanya yaitu Kantor Pertanahan seringkali menolak untuk proses balik nama apabila Akta Jual Beli yang dibuat PPAT didasari dengan Kuasa Jual. Untuk menghindari hal tersebut, Notaris menyisipkan klausul kuasa jual dalam Perjanjian Ikatan Jual Beli. Dari kesimpulan tersebut disarankan agar kuasa jual disikapi secara bijaksana oleh kantor pertanahan.Kata Kunci: Kuasa jual; PIJB; Balik Nama